Do Elderly Patients With Stage I–II Hepatocellular Carcinoma Benefit From More Radical Surgeries? A Population-Based Analysis - Zhang, Qiu-Qiang; Wu, Pan-Yi-Sha; ALBahde, Mugahed; Zhang, Lu-Fei; Zhou, Zhu-Ha; Liu, Hua; Li, Yu-Feng; Wang, Wei-Lin (Frontiers in Oncology, 2020)
Background and Aims: The best treatment modalities for elderly patients with stage I–II HCC (hepatocellular carcinoma) remain controversial in an era of a shortage of liver donors. Methods: From the SEER database (Surveillance, Epidemiology, and End Results program), 2,371 elderly patients were sampled as Cohort 1. OS (Overall Survival) and CSS (Cancer-Specific Survival) were compared between the Non-surgery and Surgery groups. A stratification analysis in a CSS Cox model was also conducted among sub-groups, and propensity score matching was performed to generate Cohort 2 (746 pairs), reducing the influences of confounders. Results: For Cohort 1, the median follow-up times of the Non-surgery and Surgery groups were 11 months (95% CI, confidence interval: 9.74–12.26) vs. 49 months (44.80–53.21) in OS, and 14 months (12.33–15.67) vs. 74 months (64.74–83.26) in CSS, respectively. In the stratification analysis, for the elderly patients (age >= 70 years), Larger Resection was associated with a higher HR (hazard ratio) than Segmental Resection: 0.30 (95% CI, confidence interval: 0.22–0.41) vs. 0.29 (0.21–0.38) in 70–74 year-olds; 0.26 (0.18–0.38) vs. 0.23 (0.16–0.32) in 75–79 year-olds; 0.32 (0.21–0.49) vs. 0.21 (0.13–0.32) in those 80+ years old. For Cohort 2, a similar result could be seen in the CSS Cox forest plot. The HRs of Larger Resection and Segmental Resection were 0.27 (0.21–0.33) and 0.25 (0.20–0.31), respectively. Conclusions: It is cautiously recommended that, when liver transplantation is not available, segmental or wedge liver resection is the better treatment choice for elderly patients with stage I–II HCC (AJCC edition 6), especially those over 70 years old, compared with other surgeries, based on the SEER data.